„Widzialny porządek” czy „ukryty wymiar”? Haiku-images Stanisława Grochowiaka - Krawczyk, Anna (Postscriptum Polonistyczne, 2020)
The article is dedicated to Haikuimages, the last poetic work of Stanisław Grochowiak. The author attempts to show how difficult it is to read oriental type of poetry, even if we know its structure and philosophical base. The only thing that we can do is to find common places between haiku and European tradition. The author points to grotesque, surrealism, imagism and magic realism. There are similarities between Grochowiak’s last poetic work and Jacek Yerka’s magic realism in painting. This leads to conclusion that Haikuimages is still an important poetic voice concerning reality and world we live in.